Evaluasi Pasca Diklat Kepemimpinan Tingkat III Tahun 2018 Pusdiklat Perdagangan Kementerian Perdagangan - Caterin Magdalena Simamora (Cendekia Niaga, 2019)
This research was conducted to evaluate the implementation of Level III Leadership Training (Diklatpim) in 2018. This study used a quantitative method with a descriptive approach. The purpose of this study is to evaluate aspects Diklatpim III. The education and training components being evaluated are the improvement of alumni performance, organization, behavior change, curriculum and the constraints to completing the change project (final project). This research shows that Diklatpim level III in 2018 has been running well and in accordance with specified criteria although there are still some obstacles in the follow-up to the medium to long term output, one of which is the problem of promotion and mutation.